Biomes, geology and past climate drive speciation of laminate-toothed rats on South African mountains (Murinae: Otomys). Issue 3 (25th November 2019) - Taylor, Peter John; Kearney, Teresa; Dalton, Desire Lee; Chakona, Gamuchirai; Kelly, Christopher M R; Barker, Nigel P
Abstract: Mitochondrial DNA sequences (1137 bp) of the cytochrome b gene and craniodental and craniometric data were used to investigate the evolutionary relationships of six putative rodent taxa of Otomys (family Muridae: subfamily Murinae: tribe Otomyini) co-occurring in the Western Cape and Eastern Cape provinces of South Africa. Phylogenetic analysis of 20 new sequences together with craniodental and craniometric characters of 94 adult skulls reveal the existence of a unique lineage of Otomys cf. karoensis (named herein Otomys willani sp. nov. ) from the Sneeuberg Centre of Floristic Endemism in the southern Drakensberg Mountain Range. Craniometric analysis distinguished O. karoensis from O. willani and identified a further four localities in the range of the latter species. We document southern range extensions of both Sloggett's ice rat, Otomys sloggetti, and the vlei rat Otomys auratus to the Sneeuberg Mountain Range, in addition to appreciable genetic divergence between Sneeuberg and southern and central Drakensberg populations of O. sloggetti . Our results demonstrate parallel patterns of cryptic speciation in two co-occurring species complexes ( Otomys irroratus s.l. and O. karoensis s.l. ) associated closely with the boundaries of biomes (fynbos vs. grassland biomes) and geological formations (Cape Fold Belt vs. Great Escarpment).